Literatur Review: Pengaruh Pijat Woolwich terhadap Pengeluaran Kolostrum pada Ibu Nifas Post Sectio Caesarea - Mulyaningsih, Sri; Hiola, Fidyawati Aprianti A. (STIKes Hamzar, 2025)
Colostrum is a thick, yellowish liquid that comes out on the first to the third postpartum day. Colostrum contains many anti-infective substances that will protect the baby from diseases that will infect the baby. However, the process of expelling colostrum can be influenced by the type of labor the mother chooses. The purpose of this study was to determine whether there was an effect of giving woolwich massage on colostrum expenditure in post-sectio caesarean post-section mothers. The research method used is a literature review study. Data collection using literature study. The results of the literature review show that there is colostrum expenditure in post-sectio caesarean postpartum mothers after being given a woolwich massage.